The Application of Probiotics for the Purpose of Growing Catfish (Clarias batrachus) in Malumbi Village, East Sumba - Nurbety Tarigan; Firat Meiyasa; Gian K. Efruan; Desy A. Sitaniapessy; Denisius U. Pati (Institute for Research and Community Services, 2019)
The community service activity reported in this paper was conducted in Malumbi Village, East Sumba Regency, East Nusa Tenggara. The target of this community service was the Tani Tunas Baru group and the Malumbi Farmer group. The purpose of this service was to provide knowledge and information to these two farmer groups about good and correct fish farming techniques and the application of EM-4 probiotics as feed for catfish. The activity consisted of two, namely workshop and mentoring. The service provided new knowledge and insight to the two farmer groups. The farmers were shown activities such as preparation for maintenance ponds, fertilization techniques, seed spreading techniques in new containers, good and correct feeding techniques, and water replacement systems car. In addition, assistance related to probiotic applications was also implemented. The results showed that the administration of probiotics EM-4 gave good results on the growth rate and survival of the catfish each by 18% and 80% when compared to controls. It is hoped that fish farmers in the Tunas Baru and Malumbi groups are able to apply the knowledge that they have learned.